Multiplicity : USE - uncertain states of Europe : a trip through a changing Europe - Wise, Susan (Milano : Skira editore, 2003)
Just what is Europe today ? Where does its territory end ? What will its future be like ? This book offers a surprising reply : Europe is not a continent with well-defined limits, but a single huge City. A City that embraces the most extreme differences, putting them in the midst of a few characteristics of the local space, sedimetned by centuries of history. From the Tyneside coal mines to the backstreets of Mazaro del Vallo, from the streets of Belgrade ro Paris high-rises, from the back rooms of Elche to San Marino's fake crenallated walls, from the Polish borders to the Swiss Alps, the space of Europe-City remains a 'device' filtering and organising the flow of people, goods, ideas. Europe-City space is actually one used to absorbing landscapes and foreign traditions, fashioned by endless negotiating between its countless protagonists ; a space with a high density of constructions and flows, where something new does not cancel what is already there, but adds to it like in a palimpsest. Using photographs, maps, interviews of a group of "prophets" of the European places, this book offers the image of Europe as an immense kaleidoscope, undergoing constant change owing to its inhabitants' self-organisation. With USE-Uncertain States of Europe, Multiplicity - an agency researching the urban condition - proposes a trip into the mysteries and resources of a continent that would seem to only reveal its true nature to those who choose to explore, from close up, its physical and social landscapes.
Publication on the exhibition 'Multiplicity : USE - Uncertain states of Europe' in Bordeaux, 24.11.2000-25.03.2001 and in Brussel, 26.10.2001-06.01.2002 and in Tokyo, 11/10/2001-26.01.2002
boek